Evaluation of the Finnish National Biodiversity Action Plan 1997-2005 - Auvinen, Ari-Pekka; Hildén, Mikael; Toivonen, Heikki; Primmer, Eeva; Niemelä, Jari; Aapala, Kaisu; Bäck, Saara; Härmä, Pekka; Ikävalko, Jussi; Järvenpää, Elise; Kaipiainen, Heidi; Korhonen, Kari T.; et al. (Finnish Environment Institute, 2013)
The results of the evaluation of the Finnish National Biodiversity Action Plan 1997-2005 indicate clear changes towards better consideration of biodiversity in the routines and policies of many sectors of the administration and economy. There are many indications that actors across society have recognized the need to safeguard biodiversity and have begun to adjust their practices accordingly. Several concrete measures have been undertaken in forests, agricultural habitats and in other habitats significantly affected by human activities. Biodiversity research has expanded significantly and the knowledge of Finland´s biological diversity has increased. In general, the Action Plan has supported public discussion of the need to safeguard biodiversity and this discussion has resulted in more positive attitudes towards nature conservation.So far, however, the implemented measures have not been sufficiently numerous or efficient to stop the depletion of original biological diversity. Many habitats remain far from their original state. More species will become endangered in the immediate future unless more effective and far-reaching measuresare taken. The objective of the EU to halt the decline of biodiversity by 2010 will not be achieved given the current development. Although the deterioration in biodiversity may have slowed down in several cases, many economic activities continue to have a negative impact on biodiversity. The scale of these activities is normally greater than that of the measures taken to manage and restore biodiversity.The evaluation focused on detecting changes in the administration of key sectors, analysing the recent development of biodiversity and observing interlinkages between these two. The analysis of administrative measures was based on interviews and on examining policy documents, reports and other relevant literature. The analysis covered changes in the administration of nature conservation, forestry, agriculture, land use and regional and development cooperation. The analysis of the ...